Kinematic analysis of shot putters at a Division I university - Waldera, R.; Christensen, B.; Collins, K.; Hektner, J. M.; St. Clair, J. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The purpose of this research was to examine the peak height during the flight phase and trunk kinematics during the landing phase, and their effects on throwing distance in the shot put using MOCAP. A secondary purpose was to examine differences between the throwing styles and gender. The participants were 12 university-level shot put throwers (six males, six females). A technique by trunk angle interaction effect just below the level of significance was found (p = .056). Significant relationships were found between throw distance and trunk lateral flexion, with females throwing further with more flexion toward their throwing arm (p = .022). The findings may help coaches understand kinematic positions exhibited by shot putters, the relationship to throwing distance, and differences between throwing styles and sex.